2018
DOI: 10.1111/mmi.14083
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin‐like domains of the cargo proteins are essential for protein stability during secretion by the type IX secretion system

Abstract: The periodontal pathogen Porphyromonas gingivalis secretes many potent virulence factors using the type IX secretion system (T9SS). T9SS cargo proteins that have been structurally determined by X-ray crystallography are composed of a signal peptide, functional domain(s), an immunoglobulin (Ig)-like domain and a C-terminal domain. Role of the Ig-like domains of cargo proteins in the T9SS has not been elucidated. Gingipain proteases, which are cargo proteins of the T9SS, were degraded when their Ig-like domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…17 In particular, Kgp participates in the degradation of hemoglobin, which contains heme molecules, and accordingly, kgp mutants form unpigmented colonies on blood agar plates. [18][19][20] Using colony pigmentation, we discovered a Type IX secretion system (T9SS) that mediates the secretion of gingipains [21][22][23][24][25][26][27] and also determined the mechanism by which gingipains attach to the cell surface, which involves binding with anionic polysaccharide-containing LPS (A-LPS). [28][29][30][31][32][33] In P. gingivalis, the gingipains-A-LPS-pili triad interacts with one another and is a major contributor to the pathogenicity of the bacterium.…”
mentioning
confidence: 99%
“…17 In particular, Kgp participates in the degradation of hemoglobin, which contains heme molecules, and accordingly, kgp mutants form unpigmented colonies on blood agar plates. [18][19][20] Using colony pigmentation, we discovered a Type IX secretion system (T9SS) that mediates the secretion of gingipains [21][22][23][24][25][26][27] and also determined the mechanism by which gingipains attach to the cell surface, which involves binding with anionic polysaccharide-containing LPS (A-LPS). [28][29][30][31][32][33] In P. gingivalis, the gingipains-A-LPS-pili triad interacts with one another and is a major contributor to the pathogenicity of the bacterium.…”
mentioning
confidence: 99%
“…Peptides derived from Titin ( 8990 ESDSG 8994 , 26941 EGNKDD 26946 , 6684 SSRLECKI 6691 , and 19103 VVHAGGVIRIIAYV 19116 ) and one peptide derived from striated muscle preferentially expressed protein kinase ( 2669 SCTVAVARVPGKLAPPEVPQ 2688 ) were located in Ig-like domains. The Ig-like domain was initially characterized as a structure composed of two sheets of antiparallel β strands [ 58 ]. Okano et al reported that the Ig-like domain contributed to the maintenance of the structure, activity, and stability of metagenome-derived glycoside hydrolase family 9 endoglucanase [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides derived from Titin ( 8990 ESDSG 8994 , 26941 EGNKDD 26946 , 6684 SSRLECKI 6691 and 19103 VVHAGGVIRIIAYV 19116 ) and one peptide derived from striated muscle preferentially expressed protein kinase ( 2669 SCTVAVARVPGKLAPPEVPQ 2688 ) were located in Ig-like domains. The Ig-like domain was initially characterized as a structure composed of two sheets of antiparallel β strands [59]. Okano et al reported that the Ig-like domain contributed to the maintenance of the structure, activity and stability of metagenome-derived glycoside hydrolase family 9 endoglucanase [60].…”
Section: Discussionmentioning
confidence: 99%